FABRICATION OF MAYNE'S SPACE MAINTAINER FOR PREMATURE LOSS OF DECIDUOUS TEETH - Goenharto, Sianiwati; Haula Robbi, M. Kautsar; Inayati, Eny; Setyowati, Okti; Kusdarjanti, Endang; Laksmi Lita Rosa, Mia; Sujati; Wahjuni, Sri; Redjeki, Sri; Nur Halimah, Anisa (Faculty of Vocational Studies, Universitas Airlangga, 2023)
Background: Premature loss for deciduous teeth is defined as the teeth that fall out before approaching the time of eruption of their replacement permanent teeth regardless of the reason for the loss of the teeth. The premature loss of deciduous teeth can cause the teeth next to the edentulous area to shift and lose arch space causing permanent teeth to grow abnormally. Prevention can be done by using Mayne's space maintainer so that the negative impact of premature loss does not occur. Purpose: Report the fabrication of Mayne's space maintainer in premature loss case. Case analysis: The laboratory accepted a working model with a case of premature loss in tooth 74 and was asked to make the Mayne's space maintainer. Result: This appliance consists of a molar band attached to tooth 75 with a 0.9 mm loop that is soldered on the buccal of the molar band. Conclusion: It is concluded that fabrication of Mayne's space maintainer in the case of premature loss of tooth 74 includes the preparation of a working model, adjustment of the molar band on tooth 75, making the loop, followed by soldering the loop to the molar band, finally the finishing and polishing.